Histopathologic findings characteristic of CARD14‐associated papulosquamous eruption. (26th December 2019) - Ring, Nan G.; Craiglow, Brittany G.; Panse, Gauri; Antaya, Richard J.; Ashack, Kurt; Ashack, Richard; Faith, Esteban F.; Paller, Amy S.; McNiff, Jennifer M.; Choate, Keith A.; Ko, Christine J.
Abstract: Background: Pathogenic mutations in caspase recruitment domain‐containing protein 14 (CARD14) lead to CARD14‐associated papulosquamous eruption, which shares clinicopathologic findings with psoriasis and pityriasis rubra pilaris. We aimed to describe distinguishing histopathologic features of CARD14‐associated papulosquamous eruption. Methods: This retrospective study examined the histopathologic features of specimens from patients with confirmed CARD14‐associated papulosquamous eruption and adult patients with plaque psoriasis and pityriasis rubra pilaris. Results: Lesional skin biopsies from patients with CARD14‐associated papulosquamous eruption consistently showed alternating checkerboard parakeratosis and orthokeratosis, acanthosis without acantholysis, and dilated vessels in the dermal papillae, with some cases also showing follicular plugging. Conclusion: CARD14‐associated papulosquamous eruption has a range of findings, with a predominance of features typically associated with pityriasis rubra pilaris.